Caregiver Burden And Psychosocial Factors In Mothers With Autism Spectrum Disorder Children - Izzatul Fithriyah; Magdeline Elizabeth Carrasco (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Burden experienced by mother can delayed the success of therapy to ASD children. This study aims to determine the correlation of psychosocial factors and caregiver burden in mothers with ASD children.Methods: This study was a cross-sectional analytic study on mothers with ASD children at the Children's Daycare Dr.Soetomo General Hospital. The research instrument used sociodemographic questionnaire and a Caregiver Burden Assessment (CBA). Results: This study was followed by 26 mothers with ASD children. Results: The results showed that 50% of mothers experienced moderate burdens and 34% experienced severe burdens. The results of the correlation analysis showed a significant relationship between caregiver burden and maternal age (p<0.05, r=0.316) and child age (p<0.05, r=0.274). Support and assistance from others in caring for GSA children also correlated with the mother's caregiver burden (p<0.05, r=0.118). Maternal caregiver burden is not correlated with marital status, education level, occupation, and economic status. Conclusion: Mothers with ASD children experience a psychological burden while caring for ASD children. Psychosocial support and assistance from the environment are urgently needed to reduce the caregiver burden on mothers so that they can improve the outcomes of interventions and therapy for children with ASD.